(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In total 390 species were found in lowland and mountain tundra habitats in Murmansk Region. 242 species were observed in both mountain tundra belt and zonal lowland tundra. Species diversity and composition of ecological and georgaphic groups of mosses was compared between lowland vs. mountain tundra.